DEVELOPMENT OF GEOGRAPHY TEXT BOOK MODEL BOOK WORLD GEOGRAPHY - Aksa, Furqan Ishak (Jurnal Ilmiah Ilmu Sosial, 2016)
The Development of Geography Textbooks Model Of World Geography. Research and development aims to produce geography text book material natural resources for class XI SMA designed with the model book World Geography. The procedure of research and development conducted by Dick and Carey model of which is done through 8 stages. Results of field trials showed admissions to book products reached 80.42% (efficient). Referring to the category of product feasibility textbooks developed by the National Education Standards Agency (2006), the scores can be categorized efficiently. Therefore, the product textbooks deserve to be used as teaching materials. Keywords: The Development, Geography textbooks, World Geography Model